Comparison of High and Low Phacoemulsification Parameter in Safety and Patients Comfort - Dian Eka Putri; Bondan Harmani; Amir Shidik; Muchtaruddin Mansyur (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To compare phacoemulsification (phaco) setting parameters with high (H) and low (L)parameters in Cipto Mangunkusumo (CM) hospitals impacted on corneal endothelial cell and patientâ€™spain perception (PP) during phaco procedure.Methods: Forty eight outpatients were eligibly selected by RCT at CM hospital in periods ofNovember 2013 to April 2014. Impacts of setting parameter difference were observed by objectivemeasurement of endothelial cell density (ECD), central corneal thickness (CCT). The PP wasmeasured by a JCI approved standard using visual analog scale (VAS) were adapted. A built-insoftware for phaco US energy count which is cumulative dissipated energy (CDE) used to objectivelytimed the phaco time, duration of operation (DO) were timed, and standard visual acuity (VA) wasalso noted. Data analysis was performed using general linear model (GLM) repeated measures.Results: Increase of CCT and decrease of ECD after 1 month in high and low phaco parameter are notsignificantly different, respectively 0.23% vs 2.23% and 8.53% vs 6.99% (p>0.05). Significantdifference were found in CDE between H and L; 15.80 vs 21.29 (p=0.015). No statistically significantdifference of VAS nor DO and VA.Conclusion: High and low parameter phacoemulsifications have an equal result in safety and patientâ€™scomfort.Â Keywords: setting phaco machine, endothelial cell density, central corneal thickness, visual analog scale